Trends in prevalence and burden of depressive disorders in Iran at national and subnational levels: estimates based on sex and age groups - Amiri, Sohrab; Khan, Moien A B (General psychiatry, 2025)
BackgroundMental disorders rank among the leading contributors to the global disease burden, with depressive disorders being among the most prevalent.AimsThe objective of this study is to examine the prevalence, incidence and years lived with disability (YLDs) associated with depressive disorders, particularly major depressive disorder and dysthymia, in Iran from 1990 to 2021. To achieve this, the research focused on analysing these metrics across various dimensions, including temporal trends, sex differences, age categories and subnational regions.MethodsThe data used in this study are sourced directly from the Institute for Health Metrics and Evaluation, ensuring that the information is both authoritative and reliable. All-age count estimates and age-standardised rates (per 100 000) were calculated for prevalence, incidence and YLDs. The disease burden indicators were analysed for the period spanning from 1990 to 2021, stratified by sex, age and location. The percentage change between 1990 and 2021 was also documented. The 95% uncertainty interval (UI) was reported for each of the reported estimates.ResultsThe prevalence of depressive disorders in Iran demonstrated a notable upward trend from 1990 to 2021, with the rate of growth being particularly pronounced within the country. The age-standardised prevalence rate per 100 000 individuals for depressive disorders in Iran was 5609 (95% UI 4810 to 6488). By 2021, the number of depression cases in Iran reached 5.2 million, which is approximately 2.37 times the figure reported in 1990. The prevalence of depressive disorders was notably higher among females compared with males. The age-standardised prevalence rate per 100 000 individuals for males was 4184 (95% UI 3545 to 4929). For females, this figure was significantly greater, reaching 7077 (95% UI 6115 to 8172). Out of the total reported cases of depressive disorders in Iran, 3.2 million were observed in females, while males accounted for 2 million cases.ConclusionsThe findings highlighted the considerable impact of depressive disorders in Iran, both nationally and regionally, while also revealing variations across sex and age groups. Given the shifts in the demographic structure and the growing burden of these disorders, it is essential to prioritise screening initiatives, education programmes and strategies aimed at enhancing mental health awareness and ensuring improved access to mental health services in health policy planning.